El declive y las mutaciones de la institución - Dubet, François (Revista de Antropología Social, 2007)
This paper deals with the institutional form of school education. For a long time, this form was built as a program structuring a symbolic economy, itself characterized by four principles: “sacred” values, vocation of the masters, school sanctuary, liberation through discipline. The transformations of school in modern societies induce the decline of this institutional program and generate a deep feeling of crisis for the actors. Beyond this crisis, it is important to define the issues linked to this transformation and the obligation that the institution has to become more democratic and more political.
Keywords: Education; Institution; Socialization; Vocation